Assessing the applicability and outcomes of the COMPASS trial a large cohort of atherosclerotic disease patients. (14th October 2021) - Welsh, R; Dover, D; McMurtry, M S; Bainey, K R; McAlister, F; Kaul, P
Abstract: Background: Atherosclerotic Cardiovascular disease (ASCVD) is the leading cause of morbidity and mortality worldwide with substantial impact on health care resources. Rivaroxaban 2.5 mg twice daily with low dose ASA reduced death, myocardial infarction and stroke compared to ASA alone in stable ASCVD patients studied in the COMPASS trial. Purpose: To assess the applicability and potential outcomes of applying the COMPASS antithrombotic strategy in a population-based cohort of patients with ASCVD. Methods: All patients with a new diagnosis of ASCVD identified during hospital admission or outpatient medical encounters using validated case definitions from 2008–2019 were included. We determined the proportion who met COMPASS eligibility criteria (Eligible), the proportion who met inclusion criteria but had exclusion criteria (Excluded), and the proportion who did not meet inclusion criteria (Ineligible). Primary outcomes of interest were CV death, myocardial infarction, and stroke (MACE), with secondary outcomes all cause death, CV hospitalization, PAD intervention, amputation, and all bleeding which were followed to end of study. Results: Of 226, 446 new ASCVD patients in the 11 years studied, 73% had coronary artery disease, 17% had peripheral artery disease including cerebral and peripheral vascular disease (PAD), and 10% had both. Of the 364, 442 prevalent cases, 27% met COMPASS eligibility criteria, another 42% met inclusion criteria but would have been excluded and 31% were Ineligible. The main reasons for exclusion were high bleeding risk characteristics in 69% and concomitant medical therapy (CYP3A4 inducers 30%, oral anticoagulants 28%, and dual antiplatelet therapy 7%). The MACE event rates were approximately twice as high in the excluded group as those deemed COMPASS eligible (figures 1). COMPASS eligible patients in our cohort exhibited event rates similar to the ASA arm of COMPASS (figure 2). The other event rates per 100 person-years for Eligible, Excluded, and Ineligible patients respectively were: all-cause death 4.6, 10.6, 1.2, ; CV hospitalization 4.8, 8.8, 3.0; PAD intervention 0.6, 0.6, 0.1; and all bleeding 1.9, 4.3, 1.1. If the COMPASS antithrombotic strategy of Rivaroxaban 2.5 twice daily with low dose ASA was given to patients deemed eligible in this population, there would have been a potential reduction of 87 MACE events, 34 CV death, 25 MI, 24 stroke, and 12 amputations per 10, 000 patient years of treatment. Conclusion: In a population of 4.4 million persons, there are approximately 20, 000 incident ASCVD patients diagnosed yearly. Approximately 70% of patients with ASCVD in the real-world met COMPASS inclusion criteria, although more than half would be excluded due to high-bleed risk characteristics or concomitant medical therapy. Implementing the COMPASS antithrombotic strategy would result in substantial reduction in CV death and MACE events. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bayer